Piagam Madinah Dan Resolusi Konflik Di Indonesia - Mu'adil Faizin (Postgraduate State Islamic Institute (IAIN) Metro, 2017)
Indonesia is known as a country which has Muslims of the major society. Unfortunately, getting a lot of conflict cases. When Indonesia gets conflicts, the Gospel of Islam and the Muslims always is blamed as the cause. Although, Islam gets the history of getting peace in practice of The Constitution of Medina. Consequently, the researcher discusses The Constitution Of Medina And A Resolution Conflict In Indonesia . The research is library research which uses the analysis method to content analysis. The research discovers that principle of The Constitution of Medina were Quran and Sunnah as the agreement inspiration; social unity; freedom of religion and movement; deliberation and autonomous leadership; helpful; humanity and social justice; and state sovereignty. Then, patterns of a resolution conflict of The Constitution of Medina that can become reference for Indonesia is dialog, tolerance and cooperation